Enhanced proton conductivity in amino acid based self-assembled non-porous hydrogen-bonded organic frameworks - Pramanik, Titas; Anand, Ashish; Pandikassala, Ajmal; Illathvalappil, Rajith; Kurungot, Sreekumar; Row, T. N. Guru (Chemical Communications, 2022)
beta-Alaninium oxalate hemihydrate, glycinium oxalate, and L-leucinium oxalate salt-cocrystals as non-porous self-assembled hydrogen-bonded organic frameworks afforded proton conductivity of 2.43 x 10(-2) S cm(-1) (60 degrees C, 95% RH), 3.03 x 10(-2) S cm(-1) (60 degrees C, 95% RH), and 1.19 x 10(-2) S cm(-1) (80 degrees C, 95% RH), respectively. These materials possess an extensive 3-dimensional network of hydrogen bonds in their crystal structures, making them efficient proton conducting membranes. The reduction in conductivity values over 10(-1) S cm(-1) order upon exposure of the samples to a D2O atmosphere in extreme conditions ratified the role of humidity for the conduction of protons. This work explores the relationship between structural features and proton conductivity for the design of proton conducting membranes that are easy to synthesize, eco-friendly, and cheap with potential for futuristic applications.